Comparison of Different Structural Software for Multistory Building Design in Terms of Concrete Columns Reinforcement - Chaw, Kit Teng (Universiti Teknologi Petronas, 2005)
The use of computers for the analysis and design of structures has become a standard practice in today's world especially in the design of complex structures, such that space craft, aircraft, tall building, long span bridges, etc. As a result of standard practice of computational design of tall building structures, there are a number of software in the market for a solution of similar problem; however, there is not exist any comparative analysis among commercially available software for tall building design. This research study was focused on the comparative analysis of different software. The comparison wasmadein terms of efficiently, ease in modelling and economy of design. Structure model with different combination of building height and bay width were used to carryout the analytical study. In orderto maintain the consistency and accuracy of the results output, columnsizes were kept constantfor all the models. Two software, Prokon Version Wl.1.02 and STAAD Pro 2002 which are very common in the structural practices in Malaysiawere used for this comparative analysis. Based on the analytical and structural design results, STAAD Pro 2002 is found to be more superior to Prokon Version Wl.1.02 in term of tall building modelling. STAAD Pro software proved to be an highly efficiency software, which produced more economical design as compared to Prokon. Moreover, the differences, similarities as well as the limitations of both programs have been identified in this project. On the whole, STAAD Pro software is a more advance program which is appropriate for tall building modelling purposes.